EXPLORING HUMAN NATURE AND EDUCATION THROUGH PHILOSOPHICAL ANTHROPOLOGY: A HUMANIST PEDAGOGICAL APPROACH AT MADRASAH TSANAWIYAH NEGERI 2 CIANJUR - Ahmad Dimyati Ridwan; Nursani Awal Artha Nugraha; Nurti Budiyanti; Pitra Gosha Patriasya; Sephia Musyaffa Nur Aulia (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This article analyses the nature of humans and education from a philosophical anthropological perspective to develop a humanist pedagogical paradigm, using a case study at MTsN 2 Cianjur. This study is motivated by the view that humans are multidimensional beings who require holistic development of their potential. At the same time, education that is solely cognitive in nature produces a crippled generation and loses the meaning of humanity. Humanist pedagogy presents an alternative, positioning students as dialogical subjects and integrating moral and spiritual dimensions. This research uses a descriptive qualitative approach, drawing on literature, observations, interviews, and documentation. Data are analysed by integrating the frameworks of philosophical anthropology, humanist pedagogy, and Islamic educational practices. The results of the study at MTsN 2 Cianjur indicate that human nature is understood comprehensively. Students are not only seen as recipients of knowledge, but as potential beings who must be developed intellectually, morally, socially, and religiously. This paradigm is realised through participatory learning, dialogical teacher-student communication, and religious habits (such as congregational prayer and tadarus), which enrich universal humanism with a transcendental Islamic dimension. This article concludes that this integration strengthens Islamic education, making it more humanistic, transformative, and relevant to the challenges of the times.